PENGARUH PENAMBAHAN ABU JERAMI PADI TERHADAP KUAT TEKAN BETON - Adytia Eko Sutrisno; Dwi Kartikasari (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Cement is one of the main ingredients in the manufacture of concrete. The raw material is used in the manufacture of cement are limestone, silica sand, clay and iron sand. Cement is a material made of material that belong to natural resources that cannot be renewed, so that the raw material inventory of cement in nature is getting less. Continuous mining of cement raw materials has an impact on natural damage. It encourages the discovery of alternative materials as an additive to the manufacture of concrete. The method of data analysis begins with the investigation of cement material, coarse aggregate, fine aggregats and rice straw ash. Concrete is added with rice straw ash with variations of 0%, 5%, 10%, and 15% additions. The test specimen are cylinders with size ø 15 cm x 30 cm and the planned compressive strength is 14.5 MPa. After going through the treatment period for 7 days, the value of compressive strength is then correlated to the age of 28 days. Based on research that has been done at Civil Engineering Laboratory of Islamic University of Lamongan, it is found that there is a decrease of strength on each addition of ash straw content of paddy. Use of rice straw ash in concrete mix with variation of 0%, 5%, 10%, and 15% addition of The weight of cement has an impact on the decrease of concrete strength value. The compressive strength values obtained at the age of 28 days are 18,440 Mpa, 15,366 Mpa, 13,948 Mpa, and 12,530 Mpa.